Advancements in functional tetrahedral DNA nanostructures for multi-biomarker biosensing: Applications in disease diagnosis, food safety, and environmental monitoring - Yun Qiu; Yixing Qiu; Wenchao Zhou; Dai Lu; Huizhen Wang; Bin Li; Bin Liu; Wei Wang (Materials Today Bio)
Deoxyribonucleic acid (DNA) offers the fundamental building blocks for the precisely controlled assemblies due to its inherent self-assembly and programmability. The tetrahedral DNA nanostructure (TDN) stands out as a widely utilized nanostructure, attracting attention for its high biostability, excellent biocompatibility, and versatile modification sites. The capability of DNA tetrahedron to interact with various signal outputs makes it ideal for developing functional DNA nanostructures in biosensing platforms. This review highlights recent advancements in functional tetrahedral DNA nanostructures (FTDN) for various biomarkers monitoring, including nucleic acid, protein, mycotoxin, agent, and metal ion. Additionally, it discusses the potential of FTDN in the fields of disease diagnosis, food safety, and environmental monitoring. The review also introduces the application of FTDN-based biosensors for simultaneous identification of multiple biomarkers. Finally, challenges and prospects are addressed to provide guidance for the continued development of FTDN-based biosensing platforms.